Організаційно-економічний механізм корпаративної взаємодії в рамках корпоративної структури "МЕТЗАЛМАШБУДЕНЕРГО" - Посохов, Ігор Михайлович (Український державний університет залізничного транспорту, 2014)
У статті розглядаються питання створення корпоративної структури "МЕТЗАЛМАШБУДЕНЕРГО" на засадах державно-приватного партнерства і побудови організаційно-економічного механізму корпоративного взаємодії в рамках створюваної корпоративної структури, визначено його сутність, виділені внутрішній і зовнішній рівні корпоративного взаємодії, розкрита структура кожного з рівнів, а також обґрунтовані результати забезпечення ефективності корпоративного взаємодії на внутрішньому і зовнішньому рівнях.

In the article the issues of creating a corporate structure "METZALMASHBUDENERGO" on principles of state-private partnership and build organizational-economic mechanism of corporate interaction in the framework of the established corporate structure, its essence, a dedicated internal and external levels of corporate interaction, revealed the structure of each of the levels, and evidence-based findings ensure the effectiveness of corporate interaction of the domestic and external levels. Under the organizational-economic mechanism of corporate interaction of "METZALMASHBUDENERGO" offers to understand the system of sustainable economic relations on the internal and external levels of corporate interaction, aimed at ensuring the effectiveness and minimize the risks of the business activities of each of the members created inside the body corporate.
Organizational-economic mechanism of corporate interaction within the corporate structure "METZALMASHBUDENERGO"
Keywords: зовнішній рівень; внутрішній рівень; державно-приватне партнерство; залізничний транспорт; corporate structure; external level; mid level